Nitranion as intermediate in the decomposition of azides electrocatalytically synthesized. A CASSCF and CASPT2 study - Soto-Martín, Juan (ELSEVIER, 2025)
In this work, we propose that nitranion (nitrene negatively charged) is an intermediate in the decomposition of azides electrocatalytically synthesized. This assertion is based on CASSCF and CASPT2 calculations, which show that (1) the radical anion of (1-azidovinyl)benzene is energetically most stable than its neutral partner [13 kcal/mol]; (2) the azidic radical anion decomposes into nitranion and molecular nitrogen after surmounting a very low barrier [4 kcal/mol].
Keywords: Química física; Azidas; Catálisis; Nitranion; Azidas; Electrosíntesis; Química física; CASSCF; CASPT2